Untitled - Carranza, Leonarda (UnderCurrents: Journal of Critical Environmental Studies, 2002)
One thing that we all agree on, is that it was dark when we left El Salvador. Some think it was night, evening, or just before day break. But all those that have a memory of that day in May remember that it was dark.